Finite element modelling of reinforced concrete slab at elevated temperature using ABAQUS - Ab. Kadir, Mariyana Aida (2014)
This paper investigates the finite element modelling of the temperature distributions of reinforced concrete slab using a general purpose non-linear finite-element program, ABAQUS. The reinforced concrete slab is tested under exposure to designed fire in order to validate the shell element in in the ABAQUS program. The modelling results showed agreement with the fire test and it demonstrated that the ABAQUS shell element can be used to predict fire behaviour within reinforced concrete slab in elevated temperature conditions.